Electrically tunable terahertz resonance in antiferromagnetic NiO/Pt heterostructures - Yang, Dongsheng (2023)
Antiferromagnets that facilitate terahertz (THz) spin resonances have the potential to revolutionize high-speed electronics at the nanoscale. The electrical control of THz spin resonances is the key to such THz devices; however, experimental demonstration has remained elusive. In this work, we demonstrate electrically tunable THz spin resonance in an antiferromagnetic NiO/Pt heterostructure by employing both low-wavenumber Raman and continuous-wave THz spectroscopy techniques. A redshift of over 100 GHz in the NiO spin resonance frequency of around 1 THz is observed by applying charge currents along the adjacent Pt layer. A control experiment with NiO/Cu and temperature-dependent measurement confirm that the dominant tuning mechanism is Joule heating. Finally, a prototype device is designed to achieve an electrical control of THz transmission at dual channels of 0.96 and 1 THz, leading to a Q factor of 56. This work opens up the possibility for the implementation of tunable THz devices utilizing antiferromagnetic spin resonance.